2007
DOI: 10.1002/gps.1954
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain and depression among geriatric psychiatry inpatients

Abstract: Chronic pain--common in depressed older adults--may influence clinical features of depression and should be assessed as a possible suicide risk factor. Prospective studies should examine causal relationships and determine the effects of adequate pain treatment on depression course and suicide risk in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
(36 reference statements)
4
33
0
Order By: Relevance
“…52 Second, in comparison to those without chronic pain, individuals with chronic pain have twice the risk for suicide. 53 Among depressed inpatients 54 and outpatients, 51 chronic pain increases the risk of suicidal ideation. Third, comorbid chronic pain and depression is associated with more disability than either condition alone.…”
Section: Discussionmentioning
confidence: 99%
“…52 Second, in comparison to those without chronic pain, individuals with chronic pain have twice the risk for suicide. 53 Among depressed inpatients 54 and outpatients, 51 chronic pain increases the risk of suicidal ideation. Third, comorbid chronic pain and depression is associated with more disability than either condition alone.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Depression has been reported to be a common problem in the geriatric population living in nursing homes, and has been shown to be associated with chronic pain. [5,[24][25][26] Bair et al demonstrated that moderate to severe pain was associated with more depressive symptoms and worse depression outcomes. [24] A study by Ohayon et al also showed chronic pain was associated with a higher severity of depression, longer episode duration, and a greater likelihood of certain depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another factor related to the presence of chronic pain is insomnia and unrefreshing sleep, which tend to worsen as the level of pain increases. 19,25 Since the elders of our study have shown a low pain level, it was expected to observe a better sleep quality, and in fact they did not complain of sleep problems.…”
Section: Discussionmentioning
confidence: 83%
“…19 It has been shown that chronic pain has impact on the psychosocial aspects, 20 and chronic (non-respondant) pain patients have higher levels of depression. 21 The relationship between pain and depression severity was the target of a paper that found an influence of personality characteristics.…”
Section: Discussionmentioning
confidence: 99%